2007
DOI: 10.1074/jbc.m706162200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Line Tension on the Lateral Organization of Lipid Membranes

Abstract: The principles of organization and functioning of cellular membranes are currently not well understood. The raft hypothesis suggests the existence of domains or rafts in cell membranes, which behave as protein and lipid platforms. They have a functional role in important cellular processes, like protein sorting or cell signaling, among others. Theoretical work suggests that the interfacial energy at the domain edge, also known as line tension, is a key parameter determining the distribution of domain sizes, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
396
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(431 citation statements)
references
References 50 publications
35
396
0
Order By: Relevance
“…It is therefore important to ask if tH aggregation may also modulate the bilayer's physical properties, such as line tension, hydrophobic mismatch and spontaneous curvature. For a bilayer with coexisting L o and L d domains, theory (34) and experiment (35) have shown that these properties exhibit a complicated interdependence. Here we computed line tension, lipid tilt angles, and pressure profiles to highlight some of the key effects of tH clustering on the bilayer.…”
Section: Antagonistic Action Of Farnesyl and Pamitoyl Tails Segregate Thmentioning
confidence: 99%
“…It is therefore important to ask if tH aggregation may also modulate the bilayer's physical properties, such as line tension, hydrophobic mismatch and spontaneous curvature. For a bilayer with coexisting L o and L d domains, theory (34) and experiment (35) have shown that these properties exhibit a complicated interdependence. Here we computed line tension, lipid tilt angles, and pressure profiles to highlight some of the key effects of tH clustering on the bilayer.…”
Section: Antagonistic Action Of Farnesyl and Pamitoyl Tails Segregate Thmentioning
confidence: 99%
“…When considering the existence of larger and more stable membrane heterogeneities or domains, which consist of distinct lipids and proteins while excluding others, one has to identify how the system compensates for the loss in entropy (Garcia-Saez et al, 2007). The hypothesis that protein-protein and protein-lipid interactions facilitate both the upscaling and temporal stability of such lipid domains could potentially put this debate to rest (Jensen and Mouritsen, 2004;Hancock, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Proteins using this "raft pathway" would not require cytosolic sorting signals but rather would be recruited to transport vesicles by their raft affinity, i.e., their propensity to interact with specific lipids, ordered domains, or other raftembedded proteins. Because ordered phases in lipid model systems consistently have been shown to be 0.6-1.5 nm thicker than disordered domains (23,24), raft-associated transmembrane (TM) proteins would be predicted to have longer TMDs. TMD length-dependent protein sorting between coexisting lipid domains has been addressed experimentally only recently by measuring partitioning of an oligomeric toxin (perfringolysin O) with multiple (35-40) TM segments in synthetic, phase-separated liposomes (25).…”
mentioning
confidence: 99%